EXCEPTIONS TO IMMUNITY IN INTERNATIONAL CRIMINAL LAW - Ristivojević, Branislav; Samardžić, Stefan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
The paper examines the exceptions to immunity in international criminal law. It begins with an overview of the structure of this institute, including its divisions and the effects of its various types, after which the paper delves into the exceptions themselves. After a thorough review of scholarly opinions on this topic, along with a comprehensive listing of the legal practices of states that have addressed these exceptions, the paper turns to a critique of each of these exceptions. One widely accepted exception to immunity, known as “ratione materiae”, relates to the types of criminal offenses that can be prosecuted. This exception is contentious because the nature of international criminal acts is such that they are rarely committed in a private capacity. The legal practices of states, which often contradict the prevailing scientific views on this issue, suggest that judges feel a greater burden of responsibility for their decisions than scholars do. The main exception to immunity, “ratione personae”, concerns the type of court that adjudicates certain acts. This exception is largely untestable in practice because, apart from the International Criminal Court (ICC), there are no other criminal courts of "international" character. Moreover, Article 98 of the Rome Statute indicates that the ICC does not view its position as absolute or superior, and that its establishment of absolute exceptions to immunity is contingent and contractual. In conclusion, the authors assess the future of the exceptions to immunity by connecting them to two fundamental principles of international criminal law: the principle of impunity for international crimes and the principle of sovereign equality among states in international relations. Since international criminal law is often more influenced by political interests than domestic legal systems are, it is plausible that the exceptions to immunity could diminish in importance. Consequently, immunities themselves may undergo a practical renaissance, followed by a resurgence in academic interest.